Staphylococcus aureus Phenol-Soluble Modulins α1–α3 Act as Novel Toll-Like Receptor (TLR) 4 Antagonists to Inhibit HMGB1/TLR4/NF-κB Signaling Pathway - Chu, Ming; Zhou, Mingya; Jiang, Caihong; Chen, Xi; Guo, Likai; Zhang, Mingbo; Chu, Zhengyun; Wang, Yuedan (Frontiers in Immunology, 2018)
Phenol-soluble modulins (PSMs) have recently emerged as key virulence determinants, particularly in highly aggressive Staphylococcus aureus isolates. These peptides contribute to the pathogenesis of S. aureus infections, participating in multiple inflammatory responses. Here, we report a new role for S. aureus PSMs in high mobility group box-1 protein (HMGB1) induced inflammation by modulating Toll-like receptor (TLR) 4 pathway. Direct ligation of TLR4 with S. aureus PSMα1-α3 and PSMβ1-β2 was identified by surface plasmon resonance. Remarkably, the binding affinity of TLR4 with HMGB1 was attenuated by PSMα1-α3. Further study revealed that PSMα1-α3 directly inhibited HMGB1-induced NF-κB activation and proinflammatory cytokines production in vitro using HEK-Blue hTLR4 cells and THP-1 cells. To analyze the molecular interactions between PSMs and TLR4, blast similarity search was performed and identified that PSMα1 and PSMβ2 were ideal templates for homology modeling. The three-dimensional (3D) structures of PSMα2, PSMα4, PSMβ1 and δ-toxin were successfully generated with MODELER, and further refined using CHARMm. PSMs docking into TLR4 were done using ZDOCK, indicating that PSMα1-α3 compete with HMGB1 for interacting with the surrounding residues (336-477) of TLR4 domain. Our study reveals that S. aureus PSMα1-α3 can act as novel TLR4 antagonists, which account at least in part for the staphylococcal immune evasion. Modulation of this process will lead to new therapeutic strategies against S. aureus infections.